Factors associated with delay in seeking care by tuberculosis patients - Dândara Nayara Azevêdo Dantas; Bertha Cruz Enders; Déborah Raquel Carvalho de Oliveira; Caroline Evelin Nascimento Kluczynic Vieira; Ana Angélica Rêgo de Queiroz; Ricardo Alexandre Arcêncio
ABSTRACT Objective: To identify social, clinical and behavioral factors of tuberculosis patients that are associated with delay in the search for primary health care. Method: This is a cross-sectional, quantitative study conducted with 56 people on treatment for pulmonary tuberculosis in the city of Natal, in the state of Rio Grande do Norte, Brazil. The data were collected through a structured instrument. The Chi-square and Fisher tests were applied to test the association between independent and dependent variables (search time). A value of p <0.05 was set as statistically significant. Results: No social or clinical variables were statistically associated with patient delays in the search for primary health care. Among the behavioral variables, self-medication and the first health service sought had a statistically significant association with the time for seeking care (p = 0.020, and p = 0.033, respectively). Conclusion: Self-medication contributes to the delay in the search for primary health care by tuberculosis patients.